1996
DOI: 10.1246/bcsj.69.1179
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Chemiluminescence Reaction between Hypobromite and Ammonia or Urea

Abstract: The reaction kinetics, the chemiluminescence spectra, the products, and the lifetimes of emission species for the chemiluminescence reaction between hypobromite and ammonia or urea in an alkaline aqueous solution were investigated. Results show that the reaction mechanism for ammonia chemiluminescence is different from that for urea. The reaction of ammonia and hypobromite produces NO2 in the gaseous phase and NO2− in solution; however, the reaction of urea and hypobromite does not. For the reaction of ammonia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 14 publications
1
20
1
1
Order By: Relevance
“…2b) but is more broadly distributed. Furthermore, the chemiluminescence spectrum is markedly different to that reported for the 2 B 2 excited state of nitrogen dioxide, which appears to negate the previous postulate (11) that the oxidation of ammonia with hypobromite offers an alternative route to the excited intermediate that is produced in the gas-phase reaction between nitrogen monoxide and ozone. The discrepancy in the region between 700 nm and 900 nm on the spectra shown in Figs 1 and 2a is caused by the reduced sensitivity of the InGaAs detector in the visible region compared to the near-infrared (16).…”
Section: Resultscontrasting
confidence: 86%
See 3 more Smart Citations
“…2b) but is more broadly distributed. Furthermore, the chemiluminescence spectrum is markedly different to that reported for the 2 B 2 excited state of nitrogen dioxide, which appears to negate the previous postulate (11) that the oxidation of ammonia with hypobromite offers an alternative route to the excited intermediate that is produced in the gas-phase reaction between nitrogen monoxide and ozone. The discrepancy in the region between 700 nm and 900 nm on the spectra shown in Figs 1 and 2a is caused by the reduced sensitivity of the InGaAs detector in the visible region compared to the near-infrared (16).…”
Section: Resultscontrasting
confidence: 86%
“…The main products of the reaction between ammonia and hypobromite are molecular nitrogen and bromide, but small quantities of nitrogen oxides have also been detected (11). The spectral distribution of this reaction in the near-infrared appears different to that observed for the gas-phase reaction between nitrogen monoxide and ozone, but it does not provide sufficient evidence to identify the emitting species.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…The hypohalites were reported to be as the chemiluminescence reagents for the determination of ammonium ion in rainwater samples [14,15]. In this study, it was found that the voltammetric behavior in the oxidation of bromide was greatly affected by the co-existed ammonium ion.…”
Section: Introductionmentioning
confidence: 84%